Unwanted Adolescent Pregnancy From a Gender Perspective - Sulistiyanto, Henri; Nurhaeni, Ismi Dwi Astuti; Fithri, An Nisa (KnE Social Sciences, 2022)
Adolescent pregnancy is increasing annually with the rising number of teenage girls. Government policies regulating family planning pose a dilemma for couples. These policies increase the prevalence of unmet needs among adolescents. This research aimed to describe the phenomenon of adolescent pregnancy from a gender perspective, using a qualitative descriptive approach. The results showed an increase in adolescent pregnancies, specifically from 559 cases in 2017, to 684 in 2018, 897 in 2019 and 806 in 2020. The family environment, especially unhappy parents, is a determinant of unwanted pregnancy in adolescents. Early marriage is a common alternative in an effort to “improve the social image of the family in society”. This suggests that women bear the brunt of gender inequality, but gender inequality is fundamentally dangerous for everyone and ultimately detrimental to the national economy. Keywords: adolescent, unmet need, KTD, parents, gender, culture